ANALISIS PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL ANAK DIBAWAH UMUR DI PENGADILAN NEGERI DEMAK - M. Sholeh Sholeh; Sri Endah Wahyuningsih (UNISSULA Semarang, 2017)
Indonesian Welfare guarantees every citizen country, including the Protection of Child Rights which is Human Rights. For a review realize the Protection and Welfare of Children, the Government issued Law No. existence of Act No. 35 of 2014 ABOUT Amendment Act No. 23 of 2002 ABOUT Child Protection, affirming the need for weighting of criminal sanctions and penalties for the perpetrators of crimes against children, especially showed to the sexual crime is aiming to provide the Securities Jera review, as well as encouraging their concrete steps to review * Resume Physical, psychological and Social Son.This study aims to study the application of criminal sanctions against crimes of sexual violence done by adults against children, and assess consideration the judge in dropped decisions the suspect crimes of violence against children under age in the matter of number 15/pid.sus.b/2015/pn dmk. The cause of sexual violence child under age is a series of the process experienced a in a life begins from underproduction siapan of factor internal and external involving the past, treatment family, social and education sexual a bad that somebody done sexual violence against children under age and the sanctions imposed criminal the suspect criminal sexual violence against children under age reference pertaining to the act no. 35 2014. Simultaneously become consideration by the judge in court see of the extent of the capable of responsibility of his work before the law.The research was done in state court demak. The kind of research juridical sociological, the research about the sanctions imposed criminal sexual violence done adults against children in the district court demak. Of the nature of research descriptive, that is accused of the sanctions imposed crimes does the violence against children in the district court demak. A source of data using data sources primary and secondary data. Technique data collection use field studies and study literature. Analyzing in a qualitative. The research results show that district court judge Demak in applying criminal sanction in a verdict matter number : No.15/Pid.Sus.B/2015/pn Dmk. The criminal prison for 3 (three) years and to undergo confinement during 3 (three months, it is fairly for judge based on the law no. 35 years 2014). Criminal sanction prison, it is just good for the society and justice-seekers self, consideration the judge in impose sunctions criminal person, based because the defendant to be modest at the trial, aknowledge frankly and with remorse.Key Password : Criminal sunctions sexual violence child unde the age at district court Demak